Use of in-vivo confocal microscopy to assess the association of dendritiform cells with progressive trachomatous conjunctival scarring. (23rd February 2017) - Hoffman, Jeremy; Massae, Patrick; Weiss, Helen; Makupa, William; Burton, Matthew; Hu, Victor
Abstract: Background: Trachoma is the most common infectious cause of blindness worldwide. In-vivo confocal microscopy (IVCM) provides high-resolution images of the ocular surface. We have previously reported a grading system for the quantitative assessment of these images in scarring trachoma. We found that the presence of trachomatous scarring was strongly associated with the presence of dendritiform cells (DFCs). The present study assessed whether there is an association between DFCs and clinical progression in scarring. Methods: Participants with trachomatous scarring in northern Tanzania were examined at baseline and 24 months (clinical assessment, photography, and IVCM of the upper tarsal conjunctiva). IVCM images were graded according to a validated grading system. Two independent observers identified scarring progression by comparing photographs taken at baseline and 24 months. Findings: 800 participants were assessed clinically at baseline and 617 of them were re-examined at 24 months. There were 465 individuals who had photographs that could be confidently graded as having either progression or scarring, or not having progression. Progression was found to occur in 113 (24%) of the 465 individuals. IVCM images were obtained in 344 of these participants at baseline and 24 months, and 29 (8·4%) had DFCs present at baseline. The presence of DFCs at baseline was significantly associated with scarring progression (p=0·01), including adjustment for age and sex (p=0·03). Interpretation: The presence of DFCs on IVCM images is associated with progressive trachomatous conjunctival scarring. DFCs are thought to represent dendritic cells, which have a central role in mediating the immune response and potentially in the pathogenesis of trachomatous scarring. The nature of these cells warrants further investigation, potentially as a novel antifibrotic therapeutic target. Funding: Wellcome Trust senior research fellowship (to MB). National Institute for Health and Research academic clinical fellowship (to JH).